PENGEMBANGAN INSTRUMEN PENILAIAN PENDIDIKAN PROFESI GURU SEKOLAH DASAR BEBASIS HOTS - Jan Wantoro; Sutama Sutama; Siti Zuhriah; Siti Hadiyati Nur Hafida (Profesi Pendidikan Dasar, 2019)
In general, this study was aimed at developing a HOTS-based PPG assessment instrument at the Universitas Muhammadiyah Surakarta. The specific objective of this study was to design a HOTS-based PPG assessment instrument that is appropriate for PPG learning. Overall, this study uses a research and development approach. While the development of research is carried out in four stages, namely the stage of defining, designing, developing and disseminating. The results showed that the level of differentiation of the questions that had been given was still low, with the index of difficulty of the questions which were also still not satisfactory. In fact, the quality of the deception has an indication that it is considered to be lacking.